Mechanism of regulation of Hsp70 chaperones by DnaJ cochaperones - Laufen, Thomas (The National Academy of Sciences, 1999)
Hsp70 chaperones assist a large variety of protein folding processes within the entire lifespan of proteins. Central to these activities is the regulation of Hsp70 by DnaJ cochaperones. DnaJ stimulates Hsp70 to hydrolyze ATP, a key step that closes its substrate-binding cavity and thus allows stable binding of substrate. We show that DnaJ stimulates ATP hydrolysis by Escherichia coli Hsp70, DnaK, very efficiently to >1000-fold, but only if present at high (micromolar) concentration. In contrast, the chaperone activity of DnaK in luciferase refolding was maximal at several hundredfold lower concentration of DnaJ. However, DnaJ was capable of maximally stimulating the DnaK ATPase even at this low concentration, provided that protein substrate was present, indicating synergistic action of DnaJ and substrate. Peptide substrates were poorly effective in this synergistic action. DnaJ action required binding of protein substrates to the central hydrophobic pocket of the substrate-binding cavity of DnaK, as evidenced by the reduced ability of DnaJ to stimulate ATP hydrolysis by a DnaK mutant with defects in substrate binding. At high concentrations, DnaJ itself served as substrate for DnaK in a process considered to be unphysiological. Mutant analysis furthermore revealed that DnaJ-mediated stimulation of ATP hydrolysis requires communication between the ATPase and substrate-binding domains of DnaK. This mechanism thus allows DnaJ to tightly couple ATP hydrolysis by DnaK with substrate binding and to avoid jamming of the DnaK chaperone with peptides. It probably is conserved among Hsp70 family members and is proposed to account for their functional diversity.